Trends in the Prevalence of Anogenital Warts Among Patients at Sexually Transmitted Disease Clinics—Sexually Transmitted Disease Surveillance Network, United States, 2010–2016. (29th November 2018) - Mann, Laura M; Llata, Eloisa; Flagg, Elaine W; Hong, Jaeyoung; Asbel, Lenore; Carlos-Henderson, Juli; Kerani, Roxanne P; Kohn, Robert; Pathela, Preeti; Schumacher, Christina; Torrone, Elizabeth A
Abstract: Background: Approximately 90% of genital warts are caused by human papillomavirus (HPV) types 6 and 11. In the United States, HPV vaccination has been recommended for girls and women aged ≤26 years, and since 2011, for boys and men aged ≤21 years and for gay, bisexual, and other men who have sex with men (MSM) aged ≤26 years. Methods: Data were obtained from 27 clinics participating in the STD Surveillance Network. Trends in the annual prevalence of anogenital warts (AGW) from 2010–2016 were described by sex and by the sex of sex partners. Results: During 2010–2016, significant declines in the prevalence of AGW were observed in women aged <40 years, men who have sex with women only (MSW) aged <40 years, and MSM of all age categories. An inflection in trend in 2012 was noted for MSW aged 20–24 or 25–29 years and for MSM aged 20–24 years. Conclusions: The observed declines in the prevalence of AGW suggest that HPV morbidity is declining among populations attending STD clinics, including MSW, MSM, and women. Declines in younger age groups are consistent with what would be expected following the implementation of HPV vaccination. However, declines were also observed in older age groups and are not likely to be the result of vaccination. Abstract : Data from US Sexually Transmitted Disease Surveillance Network clinics revealed significant declines during 2010–2016 in prevalences of anogenital warts among women aged <40 years, men aged <40 years who have sex with women only, and men of any age who have sex with men.